Edith Holler : being her story: and containing numerous illustrations drawn from the life, private albums, and extensive card theatre collection of Edith Holler, authoress - Carey, Edward, 1970- (Riverhead Books, 2023)
"The witty and entrancing story of a young woman trapped in a ramshackle English playhouse-and the mysterious figure who threatens the theater's very survival. The year is 1901. England's beloved queen has died, and her aging son has finally taken the throne. In the eastern city of Norwich, bright and inquisitive young Edith Holler spends her days among the boisterous denizens of the Holler Theatre, warned by her domineering father that the playhouse will literally tumble down if she should ever leave its confines. Fascinated by tales of the city she knows only from afar, she decides to write a play of her own: a stage adaptation of the legend of Mawther Meg, a vicious figure said to have used the blood of countless children to make the local delicacy known as Beetle Spread. But when her father suddenly announces his engagement to a peculiar, imposing woman named Margaret Unthank, heir to the actual Beetle Spread fortune, Edith scrambles to protect her father, the theater, and her play-the one thing that's truly hers-from the newcomer's sinister designs. Teeming with unforgettable characters, and illuminated by the author's trademark fantastical illustrations, Edith Holler is a surprisingly modern fable of one young woman's struggle to escape her family's control- and to reveal inconvenient truths about the way children are used"--